Relative Performance of Various Types of Repositories for MySQL Archive Backup and Restore Operations - Petrov, Pavel; Kuyumdzhiev, Ivan; Dimitrov, Georgi; Kremenska , Adelina (International Journal of Online and Biomedical Engineering (iJOE), 2022)
The backup and restore operations are essential part of database system's administration process. Usually, the size of the database is a major factor that determines numerous practical issues, among which is what backup and recovery methods to be used. However, in addition, there are various types of storage systems (repositories) available in MySQL 8.0, for example MyISAM, Merge, Memory, InnoDB, CSV, Blackhole, Archive and Federated, which in general sense determine how to store each table into at least one file. Each of these storage systems have their own positive and negative characteristics, so when constructing logical archives, it is vital to compare the performance of those various types of repositories.